OWL: Experiences and Directions -- reasoner evaluation : 13th International Workshop, OWLED 2016, and 5th International Workshop, ORE 2016, Bologna, Italy, November 20, 2016, Revised selected papers /: 13th International Workshop, OWLED 2016, and 5th International Workshop, ORE 2016, Bologna, Italy, November 20, 2016, Revised selected papers. (2017) - Unknown
No abstract available